2013
DOI: 10.2174/15680266113139990132
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Antimicrobial Evaluation of Novel 1,3-Oxazolidin-2- one Derivatives

Abstract: A series of novel derivatives of 1,3-oxazolidin-2-one 12a-12n has been synthesized starting from 4-nitro-(L)- phenylalanine by involving five-step reaction sequence. All the compounds were screened for their in vitro antibacterial activity against four pathogenic bacterial strains namely, Staphylococcus aureus, Bacillus subtilis (Gram-positive), Escherichia coli, Pseudomonas aeruginosa (Gram-negative) and in vitro antifungal activity against two pathogenic fungal strains namely, Candida albicans and Saccharomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[27][28][29] Oxazolines are also known to have some antifungal activity against some unicellular fungi. 30,31 In another study, pyrazole carboxylic and dicarboxylic acid derivatives have shown poor anti-Candida activity, which has been related to the positions of the electronegative atoms in the pyrazole substituents and the amount of associated charges on these electronegative atoms play an important role in regulating the antifungal activity for the C. albicans strains. 32 5B and 6B are bis-pyrimidithione derivatives, whereas 5M and 6M contain a single pyrimidithione ring in their skeleton.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…[27][28][29] Oxazolines are also known to have some antifungal activity against some unicellular fungi. 30,31 In another study, pyrazole carboxylic and dicarboxylic acid derivatives have shown poor anti-Candida activity, which has been related to the positions of the electronegative atoms in the pyrazole substituents and the amount of associated charges on these electronegative atoms play an important role in regulating the antifungal activity for the C. albicans strains. 32 5B and 6B are bis-pyrimidithione derivatives, whereas 5M and 6M contain a single pyrimidithione ring in their skeleton.…”
Section: Microbiological Analysismentioning
confidence: 99%